The Effect of Different Types of Oil On Non Dairy Frozen Dessert Quality - Zainuddin, Nor Anisah; Meriam Suhaimy, Syazwan Hanani (Enhanced Knowledge in Sciences and Technology, 2023)
Ice cream is a mixture of sugar, cream, milk and sometimes other ingredients, frozen in a soft, creamy treat using a manufacturing process. Ice cream is a well-liked dairy dessert that is enjoyed by almost all people. The purpose of this study was to produce ice cream using vegetable oil, virgin coconut oil, hazelnut oil, and olive oil instead of using milk fat. The physicochemical properties such as pH, colour (L* a* b* values), moisture content, melting curve, total soluble solids (TSS), FTIR and overrun have been investigated. Ice cream that have been produced is chocolate chip ice cream. Sample of ice cream were done by using ice cream maker. Except for moisture content, significant changes in colour, pH, and total soluble solid (TSS) values between ice cream formulations were found (p